Pedicular Hamstring With 2 Adjustable Loops for Anterior Cruciate Ligament Reconstruction: The Double-Loop Technique - Kepa Iglesias, M.D.; Guillaume Robert, M.D.; Emilie Roustan, M.D.; Michel Christofilis, M.D. (Arthroscopy Techniques)
Abstract:: Pedicular hamstring grafts have become increasingly popular for anterior cruciate ligament reconstruction, preserving sufficient blood supply to enhance bone-to-tendon healing while providing additional mechanical fixation on the tibial side. This Technical Note introduces an original approach utilizing a dual adjustable loop fixation for hamstring grafts, maintaining the tibial insertion, in anterior cruciate ligament reconstruction.